Demythologizing Arctodus simus, the ‘short-faced’ long-legged and predaceous bear that never was - Figueirido-Castillo, Francisco Borja; Pérez-Claros, Juan Antonio; Torregrosa, Vanessa; Martín-Serra, Alberto; Palmqvist-Barrena, Carlos Paul (Taylor and Francis, 2010)
In this study, we review the previous evidence on the paleobiology of the giant, ‘short-faced’ bear Arctodus simus (Mammalia: Carnivora: Ursidae) and contribute new ecomorphological inferences on the paleobiology of this enigmatic species. Craniodental variables are used in a comparative morphometric study across the families Felidae, Hyaenidae, Canidae, and Ursidae. Principal components analyses (PCAs) do not show an ecomorphological adaptation towards bonecracking or hypercarnivory in the ‘short-faced’ bear. In contrast, PCAs and discriminant analyses restricted to the craniodental data set of ursids suggest close morphological resemblance between A. simus and the extant omnivorous bears. In addition, the scaling of snout length on neurocranial length in bears indicates that the face of A. simus was not particularly short. Body mass estimates obtained from major limb bone measurements reveal that A. simus specimens of around 1000 kilograms were more common than previously suspected. Scaling relationships in extant bears of limb lengths on the least width of the femoral shaft (the variable best correlated with body mass) indicate that A. simus was not as relatively long-legged as previously thought. For these reasons, although the isotopic signature of A. simus has been interpreted as evidencing that it consumed large amounts of flesh relative to some contemporary populations of Ursus arctos, our results do not support the previous views of A. simus as a fast-running super-predator or as a specialized scavenger. In contrast, the picture that emerges from this study is one of a colossal omnivorous bear whose diet probably varied according to resource availability.
Keywords: Morfometría; Arctodus simus; Morphometrics